Aprender ensinando o suporte básico de vida: a universidade além de seus muros - Sergio Geraldo Veloso (2018)
New teaching methodologies have been used to increase the acquisition and retention of knowledge, placing the student at the center of the process. Learning by teaching could be a useful teaching approach. The purpose of this study was to evaluate whether the performance of medical students (knowledge and skills) in cardiopulmonary resuscitation would improve when teaching others and if those people would actually learn from them, adopting the act of teaching as an intervention. Through a socially engaged curriculum, 92 students from the 2nd period of the medical course of the Federal University of São João del Rei, Dom Bosco Campus, were trained to carry out Basic Life Support and, in order to disseminate knowledge, they trained 240 nonphysician health professionals from Basic Health Units and Family Health Programs. Those medical students performed theoretical tests (from 0 to 20 points) and practical ones (from 0 to 17 points) (pre- and post-intervention), and the professionals from the Basic Health Units performed theoretical tests (from 0 to 20 points) before and after the Basic Life Support course and post-course practical test (from 0 to 17 points). In order to evaluate the effect of teaching on students learning, they were divided into two groups: case, with 53 students, reassessed after teaching health professionals, and control with 39 students reassessed before teaching. The initial theoretical and practical assessments of the students of the case and control groups did not show statistical difference between the groups. However, after the intervention, the practical students performance of the case group went from 13.3 ± 2.1 to 15.3 ± 1.2 (p <0.001) and theoretical from 10.1 ± 3.0 to 16.4 ± 1.7 (p <0.001). While the performance of the control group ranged from 14.4 ± 1.6 to 14.4 ± 1.4 (p = 0.877) and from 11.2 ± 2.6 to 15.0 ± 2.3 (p <0.001), respectively. The theoretical performance of health professionals from the Basic Health Units changed from 7.9 ± 3.6 to 13.3 ± 3.2 (p <0.001) and the practical performance after intervention was 11.7 ± 3.2. The students who passed through the teaching activity had a theoretical performance (p = 0.005) and practical one (p = 0.001) higher than the control. The health professionals of the Basic Health Units were able to learn with the students improving their theoretical knowledge and learning practical skills. This work demonstrated that the teaching activity can be an effective learning methodology for medical students. Besides that, it allows the dissemination of knowledge, taking the university beyond its walls in the performance of its social responsibility.